Windows 7 portable command guide : MCTS 70-680, and MCITP 70-685 and 70-686 - Gibson, Darril (Pearson IT Certification, 2011)
With hundreds of Windows 7 OS commands, options, and command arguments to remember, a MCTS 70-680, MCITP 70-685 and 70-686 candidate has a lot to commit to memory. Having an easy-to-use, portable reference filled with handy tips and examples on how to apply the commands to real-world scenarios will help increase users familiarity with Windows 7. The Windows 7 Portable Command Guide is a supplementary guide to assist administrators in the proper use of the Windows 7 OS and of the commands needed to pass the exams. The guide summarizes all Windows 7 commands, keywords, command arguments, and associated prompts. Configuration examples are provided throughout the book to give a better understanding of how these commands are used. This guide is not meant to replace any existing learning materials but rather serve as a supplementary guide to assist readers in the proper use of the many different commands that are required to successfully pass the exams. The compact, convenient Windows 7 administration command reference: every command MCTS 70-680 and MCITP 70-685/70-686 exam candidates need! Practical, example-rich, tip-filled information on every Windows 7 admin command required by Microsoft's MCTS 70-680 and MCITP 70-685/70-686 exams, plus other day-to-day admin commands Real-world scenarios that help professionals work more efficiently, and pass their exams the first time The perfect take-anywhere resource: no need to carry thick books or get on the Internet.